SlZHD17 is involved in the control of chlorophyll and carotenoid metabolism in tomato fruit. (1st December 2021) - Shi, Yuan; Pang, Xiaoqin; Liu, Wenjing; Wang, Rui; Su, Deding; Gao, Yushuo; Wu, Mengbo; Deng, Wei; Liu, Yudong; Li, Zhengguo
Abstract: Chlorophylls and carotenoids are essential and beneficial substances for both plant and human health. Identifying the regulatory network of these pigments is necessary for improving fruit quality. In a previous study, we identified an R2R3-MYB transcription factor, SlMYB72, that plays an important role in chlorophyll and carotenoid metabolism in tomato fruit. Here, we demonstrated that the SlMYB72-interacting protein SlZHD17, which belongs to the zinc-finger homeodomain transcription factor family, also functions in chlorophyll and carotenoid metabolism. Silencing SlZHD17 in tomato improved multiple beneficial agronomic traits, including dwarfism, accelerated flowering, and earlier fruit harvest. More importantly, downregulating SlZHD17 in fruits resulted in larger chloroplasts and a higher chlorophyll content. Dual-luciferase, yeast one-hybrid and electrophoretic mobility shift assays clarified that SlZHD17 regulates the chlorophyll biosynthesis gene SlPOR-B and chloroplast developmental regulator SlTKN2 in a direct manner. Chlorophyll degradation and plastid transformation were also retarded after suppression of SlZHD17 in fruits, which was caused by the inhibition of SlSGR1, a crucial factor in chlorophyll degradation. On the other hand, the expression of the carotenoid biosynthesis genes SlPSY1 and SlZISO was also suppressed and directly regulated by SlZHD17, which induced uneven pigmentation and decreased the lycopene content in fruits with SlZHD17 suppression at the ripe stage. Furthermore, the protein–protein interactions between SlZHD17 and other pigment regulators, including SlARF4, SlBEL11, and SlTAGL1, were also presented. This study provides new insight into the complex pigment regulatory network and provides new options for breeding strategies aiming to improve fruit quality.